Pengaruh Media Iklan Terhadap Keterampilan Menulis Karangan Persuasi Siswa Kelas Viii Smp Strada Marga Mulia - Angel Cano Abigael Wohingati; Yayan Sudrajat (Jurnal Pendidikan Indonesia, 2025)
This study aims to: (1) Determine the influence of advertising media; (2) Determine students' persuasive writing skills; 3) Determine the influence of advertising media on students' persuasive writing skills. The type of research used in this study is quantitative research. The sample used was 120 students. The data collection technique used a test then analyzed using statistics. The results of the study indicate that the alternative hypothesis proposed in this study can be accepted. This means that there is a significant relationship between the Influence of Advertising Media on the Persuasive Writing Skills of Class VIII Students of SMP Strada Marga Mulia. This is based on hypothesis testing at a significance level of 5% obtained tcount> ttable (1.82> 1.65) then, the author concludes that H0 is rejected and H1 is accepted. The hypothesis is proven to be true and significantly accepted.